Regulation of Genes Involved in Carnitine Homeostasis by PPARα across Different Species (Rat, Mouse, Pig, Cattle, Chicken, and Human). (23rd October 2012) - Ringseis, Robert; Wen, Gaiping; Eder, Klaus
Abstract : Recent studies in rodents convincingly demonstrated that PPAR α is a key regulator of genes involved in carnitine homeostasis, which serves as a reasonable explanation for the phenomenon that energy deprivation and fibrate treatment, both of which cause activation of hepatic PPAR α, causes a strong increase of hepatic carnitine concentration in rats. The present paper aimed to comprehensively analyse available data from genetic and animal studies with mice, rats, pigs, cows, and laying hens and from human studies in order to compare the regulation of genes involved in carnitine homeostasis by PPAR α across different species. Overall, our comparative analysis indicates that the role of PPAR α as a regulator of carnitine homeostasis is well conserved across different species. However, despite demonstrating a well-conserved role of PPAR α as a key regulator of carnitine homeostasis in general, our comprehensive analysis shows that this assumption particularly applies to the regulation by PPAR α of carnitine uptake which is obviously highly conserved across species, whereas regulation by PPAR α of carnitine biosynthesis appears less well conserved across species.